Colorado Potato Beetle, Leptinotarsa decemlineata (Say) and False Potato Beetle, Leptinotarsa juncta (Germar) (Insecta: Coleoptera: Chrysomelidae) - Richard L. Jacques, Jr. (EDIS)
True "potato beetles" are members of the beetle genus Leptinotarsa, with 32 species in North America, including Mexico; 10 species in the continental United States, including two species in Florida. The most notable is the Colorado potato beetle, Leptinotarsa decemlineata (Say), found in Florida and most of the United States, and introduced into Europe and parts of Asia. It is a serious pest of potatoes and other solanaceous plants. This document is EENY-146 (originally published as DPI Entomology Circular 271), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2000. Revised: August 2003.